COLOR, PIGMENT AND RESIDUAL NITRITE OF DENDENG SAPI NATURALLY CURED AT VARIOUS LEVEL OF CELERY LEAVES AND INCUBATION TEMPERATURES - Saputro, E.; Bintoro, V. P. Priyo; Pramono, Y. B. Budi (Journal of the Indonesian Tropical Animal Agriculture, 2016)
his study was conducted to analyze the effect of natural curing by various levels of fresh celery leaves (FCL) and various levels of incubation temperature. The incubation temperature was room temperature (RT) and temperature of 40.6oC (40.6) for 2 hours. These incubation temperatures for creating dendeng sapi were designed to provide the similar curing characteristics of the control (by addition of 50 ppm of NaNO2). Four naturally cured dendeng sapi treatments were A1 = 22 g FCL/kg of beef, RT; A2 = 36 g FCL/kg of beef, RT; A3 = 22 g FCL/kg of beef, 40.6; A4 = 36 g FCL/kg of beef, 40.6 and a treatment of conventionally cured dendeng sapi by addition of 50 ppm NaNO2 as a control (A0 ). All of the naturally cured dendeng sapi (A1-A4) showed color, cured pigment, total pigment and residual nitrite which were not significantly different compared with A0 . The FCL used in this study was an effective replacement for sodium nitrite at the test levels in manufacturing natural cured dendeng sapi. These results indicated that at fewer FCL levels (22 g/kg of beef) and a more practical of the incubation for 2 hours at room temperature were more effective to create naturally cured dendeng sapi.